Defining Engagement: A Study of Parent-Educator Perspectives - Baker, Stephanie; Andzik, Natalie (International Journal about Parents in Education, 2025)
Developing professional, reciprocal relationships between parents and educators that leads to meaningful parental engagement in schools is challenging and often the result of differing definitions of engagement and associated activities. Therefore, the purpose of this project was to investigate parent and educator definitions of parental engagement. It was further to investigate educators’ expectations for parental engagement, and whether parental engagement activities match those expectations. Parents and educators of school age children were surveyed to investigate their proposed definitions of parental engagement and associated activities. Surveys were delivered electronically to parents and educators residing and working in local schools and early care programs. An analysis of results points at similarities and differences in proposed definitions and associated engagement activities. Educator implications and characteristics important to developing parent-educator partnerships aimed at enhancing parental engagement in schools is further discussed.